Gender Equality in Arabic Language Education in the Digital Era: A Critical Analytical Study of the Al-Lughah al-'Arabiyyah al-Muyassarah Textbook at Islamic University of Pemalang - Aziz Muzayin; Rinanti; Asma Monoarfa; Suhandi Yusuf; Nazlah Muti’ah RP (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
Gender representation in educational materials has become a significant issue because it shapes learners’ perceptions of social roles and identities. Previous studies on Arabic language textbooks have largely reported gender bias, male dominance, and stereotypical portrayals of women. However, few studies have examined textbooks that promote balanced gender representation, particularly those developed within Islamic higher education institutions. This study analyzes gender equality in Al-Lughah al-'Arabiyyah al-Muyassarah, an Arabic language textbook developed by the Language Development Center of Islamic University of Pemalang. Using a qualitative approach, the research employs content analysis and Sara Mills’ feminist discourse analysis to examine five dimensions of gender representation: subject position, object position, professional role representation, activity representation, and visual representation. The findings indicate that male and female characters are represented in relatively balanced ways throughout the textbook. Female characters frequently occupy subject positions, actively participate in academic and social interactions, and appear in diverse professional roles. The textbook also presents masculine and feminine occupational forms in parallel structures while depicting women in educational, recreational, and professional activities. Visual representations further reinforce these inclusive patterns. From Sara Mills’ perspective, the textbook constructs gender equality by positioning women as active learners, professionals, and social actors rather than passive objects. The study concludes that Al-Lughah al-'Arabiyyah al-Muyassarah demonstrates the characteristics of a gender-responsive Arabic language textbook and offers a valuable model for developing inclusive Arabic language teaching materials in the digital era.Keywords: gender equality, Arabic language education, Sara Mills, feminist discourse analysis, digital era.